2019
DOI: 10.1155/2019/1529306
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Cause of Thrombotic Thrombocytopenia Purpura- (TTP-) Like Syndrome, Vitamin B12 Deficiency: Interpretation of Significant Pathological Findings

Abstract: Thrombotic thrombocytopenia purpura (TTP) is a hematological emergency that requires rapid assessment followed by prompt initiation of therapy due to high mortality associated with delayed treatment. TTP has many causes including heritable syndromes, ADAMTS13 deficiency, and drugs-related etiologies. Profound vitamin B12 deficiency can, in rare cases, mimic TTP in presentation, and since plasmapheresis can be of limited benefit, prompt diagnosis is necessary for accurate treatment with B12. Therefore, careful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Intramedullary hemolysis secondary to pseudo-folate deficiency and subsequently impaired DNA synthesis and cellular division manifests in one of two mechanisms. One mechanism may be that immature reticulocytes arrest in development and are destroyed within the marrow [ 7 , 8 ]. An alternative mechanism is impaired marrow egression.…”
Section: Discussionmentioning
confidence: 99%
“…Intramedullary hemolysis secondary to pseudo-folate deficiency and subsequently impaired DNA synthesis and cellular division manifests in one of two mechanisms. One mechanism may be that immature reticulocytes arrest in development and are destroyed within the marrow [ 7 , 8 ]. An alternative mechanism is impaired marrow egression.…”
Section: Discussionmentioning
confidence: 99%
“…Cobalamin deficiency cannot only lead to ineffective erythropoiesis but can also increase red blood cell rigidity, which can in turn promote intramedullary destruction of red cell precursors [7]. As the erythrocyte precursor cells are nucleated and contain very little hemoglobin, lysis of these cells translates into laboratory findings of very high LDH (>2,500 IU/L), reticulocytopenia and relatively normal bilirubin which can be used to distinguish from TTP [1,8]. Additionally, cobalamin deficiency can increase homocysteine levels in the blood, which is associated with endothelial injury, vasoconstriction, stimulation of the coagulation cascade and increased platelet aggregation, all of which can promote intravascular hemolysis [7].…”
Section: Discussionmentioning
confidence: 99%
“…48 In a study of 201 patients with CD, pseudo-TMA was reported in 2.5% of patients, 45,49 which can potentially lead to misdiagnosis of thrombotic thrombocytopenic purpura (TTP) and wrong treatment with plasma exchange. 50,51 One study depicted that pseudo-TMA patients had higher mean LDH levels, higher mean platelet counts, lower mean reticulocyte count, and lower mean neutrophil counts, compared to patients with true TTP. Other clues on PBS examination pointing against the diagnosis of TTP include the presence of HSNs and macroovalocytes.…”
Section: Pa Presenting With Pseudo-thrombotic Microangiopathy (Pseudo-tma)mentioning
confidence: 99%
“…Cytoskeletal fragility of erythroblasts may contribute to schistocyte formation in megaloblastic anemia, depending on the severity of dyserythropoiesis 48 . In a study of 201 patients with CD, pseudo‐TMA was reported in 2.5% of patients, 45,49 which can potentially lead to misdiagnosis of thrombotic thrombocytopenic purpura (TTP) and wrong treatment with plasma exchange 50,51 . One study depicted that pseudo‐TMA patients had higher mean LDH levels, higher mean platelet counts, lower mean reticulocyte count, and lower mean neutrophil counts, compared to patients with true TTP.…”
Section: Challenging Clinical Presentations Which Make the Diagnosis Of Pa Very Difficultmentioning
confidence: 99%